Poverty Effects of Higher Food Prices : A Global Perspective - De Hoyos, Rafael E.; Medvedev, Denis (2012)
The spike in food prices between 2005 and the first half of 2008 has highlighted the vulnerabilities of poor consumers to higher prices of agricultural goods and generated calls for massive policy action. This paper provides a formal assessment of the direct and indirect impacts of higher prices on global poverty using a representative sample of 63 to 93 percent of the population of the developing world. To assess the direct effects, the paper uses domestic food consumer price data between January 2005 and December 2007--when the relative price of food rose by an average of 5.6 percent --to find that the implied increase in the extreme poverty headcount at the global level is 1.7 percentage points, with significant regional variation. To take the second-order effects into account, the paper links household survey data with a global general equilibrium model, finding that a 5.5 percent increase in agricultural prices (due to rising demand for first-generation biofuels) could raise global poverty in 2010 by 0.6 percentage points at the extreme poverty line and 0.9 percentage points at the moderate poverty line. Poverty increases at the regional level vary substantially, with nearly all of the increase in extreme poverty occurring in South Asia and Sub-Saharan Africa.